2019
DOI: 10.1177/1741143219864937
|View full text |Cite
|
Sign up to set email alerts
|

The role of leadership in establishing a positive staff culture in a secondary school

Abstract: This Australian case study explored the implementation of strategies to support the development of a positive school culture among whole school staff. A participatory action research approach was used to involve leadership staff in the development of a mixed method assessment of the school organisation. Baseline data from the School Organisational Health Questionnaire (n ¼ 28) and qualitative data from focus groups (n ¼ 15) were collected and presented to the leadership team who identified four foci for the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Research suggests that a more democratic and participative decision-making style may contribute to higher levels of morale (Brown et al, 2002; Jago, 1982; Morris et al, 2019; Wadesango, 2012). In this study, the decision-making style of the leadership was found to be likely impacting morale and burnout.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that a more democratic and participative decision-making style may contribute to higher levels of morale (Brown et al, 2002; Jago, 1982; Morris et al, 2019; Wadesango, 2012). In this study, the decision-making style of the leadership was found to be likely impacting morale and burnout.…”
Section: Resultsmentioning
confidence: 99%
“…Morris et al (2019) investigated strategies useful to increase morale and staff well-being. They concluded that a change in leadership style is a key factor in increasing school morale.…”
Section: Moralementioning
confidence: 99%
“…The way educational services are provided and managed is changing, including the way, teaching practices are managed to solve problems of competitive educational programs. These programs bring innovative components to school life practice [15]. The study results complement the data on the impact of distributed leadership on teacher job satisfaction and self-efficacy.…”
Section: Discussionmentioning
confidence: 54%
“…Second, to ensure that change processes are sustainable, teaching staff need to share a commitment to school improvement: Here, teacher collaboration catalyzes the sharing and processing of information about common visions and goals (Seashore Louis & Lee, 2016). Third, principals and leadership teams need to provide teachers with opportunities for participation in decision making processes so that teachers have a voice and feel empowered (Austin & Harkins, 2008;Morris et al, 2020). Fourth, organizational learning requires knowledge and skills that members of the school community or other individuals (e.g., principals, teachers, or external experts) either bring with them or acquire through training or other learning opportunities.…”
Section: Theoretical Framework Of Organizational Learning and Organiz...mentioning
confidence: 99%